2013
DOI: 10.2139/ssrn.2333590
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring and Relative Labor Demand from a Task Perspective

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
4
6
0
Order By: Relevance
“…Becker et al (2013) found that offshoring is associated with a downward shift of labour demand towards less-routinized and interactive tasks, and with an upward shift towards highly qualified workers. Similar results have been found by Hogrefe (2013) showing that offshoring has shifted domestic labour demand towards complex tasks, in particular when offshoring is directed towards non-OECD countries. Different results are however found by Akcomak et al (2013) showing that offshoring changes the level of employment without affecting the way in which tasks are organized.…”
Section: Gvc Integration Offshoring and Employmentsupporting
confidence: 85%
“…Becker et al (2013) found that offshoring is associated with a downward shift of labour demand towards less-routinized and interactive tasks, and with an upward shift towards highly qualified workers. Similar results have been found by Hogrefe (2013) showing that offshoring has shifted domestic labour demand towards complex tasks, in particular when offshoring is directed towards non-OECD countries. Different results are however found by Akcomak et al (2013) showing that offshoring changes the level of employment without affecting the way in which tasks are organized.…”
Section: Gvc Integration Offshoring and Employmentsupporting
confidence: 85%
“…Thus, she classifies tasks according to categories of routines, interaction and blue‐collar/white‐collar activities (three job characteristics). In the end, however, the differentiation is mostly between routine tasks and non‐routine tasks, even in papers building on her work (see, for example, Hogrefe ()). The method she uses to generate the five categories follows Autor et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Section ), to different degrees of offshoreability. For the correlation analysis presented in Table , all tasks classified as routine manual or as routine cognitive have been classified as more offshoreable (+1), whereas non‐routine analytic tasks are classified as less offshoreable (−1); tasks classified as non‐routine interactive and non‐routine manual have been classified as ambiguous (0) (similarly, see Hogrefe, ). Based on these assignments, indices of offshoreability according to Spitz‐Oener's () classification have been calculated for the (various) tasks performed by each individual…”
Section: Empirical Illustration and Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autor et al (2013b) show that predominantly routine-intensive jobs are subject to offshoring. Hogrefe (2013) finds that German manufacturing industries reduce domestic demand for routine and non-interactive tasks in response to increased offshoring.…”
Section: Skill-biased Technological Changementioning
confidence: 99%